Evaluation of an integrated multisector campaign to increase child helmet use in Vietnam. Issue 3 (25th November 2017) - Nhan, Le Dinh Trong; Parker, Lukas; Son, Mai Thi Hoai; Parker, Erin M; Moore, Matthew R; Sidik, Mirjam; Draisin, Natalie
Abstract : Objective: This study presents child helmet use before, during and after implementing the Vietnamese National Child Helmet Action Plan (NCHAP) and evaluates its effect on child helmet use. The NCHAP, an integrated multisector campaign, incorporated a wide-scale public awareness campaign, school-based interventions, increased police patrolling and enforcement, and capacity building and support to relevant government departments in target provinces. Methods: In Vietnam's three largest cities, 100 schools in 20 districts were selected to monitor motorcycle helmet use behaviour. The effectiveness of the NCHAP was measured by unannounced, filmed observations of student motorcycle passengers and their adult drivers as they arrived or left their schools at four points. Baseline observations at each school were conducted in March 2014, with subsequent observations in April 2015, December 2015 and May 2016. Results: Across the 84 218 observed students, student helmet prevalence increased from 36.1% in March 2014 to 69.3% immediately after the initiation in April 2015. Subsequent observations in December 2015 and May 2016 showed a reduction and stabilisation of helmet use, with 49.8% and 56.9% of students wearing helmets, respectively. Helmet use in students was higher when adult drivers were also wearing helmets. Conclusions: Integrated multisectoral interventions between governments, civil society and the corporate sector that incorporate communications, school-based education, incentives for change and police enforcement have the potential to increase helmet use among children. Future integrated campaigns may be more effective with an increased focus on parents and other adult drivers given their potential influence on child helmet use.